Measuring the differences in perceptions of social responsibility at Vietnam Joint Stock Commercial Bank For Industry And Trade Ba Ria - Vung Tau Branch - Tu , Thị Đức (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
Since the 1960s, the social responsibility of the business (social responsibility) has become a matter of wide interest and attention from many different subjects. Not only do social organizations, governments, academia, and academia pay attention to this aspect, but banks and customers are also increasingly interested. This stems from the increasingly popular awareness that the bank is not merely working with the profit goals but also ensures moral responsibility for employees and the community they serve. This study conducts a survey, evaluation, and comparison of differences in perceptions of corporate social responsibility (CSR) between the leadership group and the employee group working at Vietnam Joint Stock Commercial Bank For Industry And Trade Ba Ria - Vung Tau Branch (Vietinbank branch has implemented and researched not only assessing the level of the bank's commitment in fulfilling social responsibility but also identifying the difficulties and challenges they are facing. Since then, I have researched and proposed several specific solutions to improve the efficiency of social responsibility, ensure the sustainable development of the bank, and at the same time contribute more positively to the common interests of society.